NI-13 THE RATIO OF T1-WEIGHTED TO T2-WEIGHTED SIGNAL INTENSITY AND IDH MUTATION IN GLIOMA. (3rd December 2022) - Sanada, Takahiro; Yamamoto, Shota; Sakai, Mio; Umehara, Toru; Sato, Hirotaka; Saito, Masato; Mitsui, Nobuyuki; Hiroshima, Satoru; Anei, Ryogo; Kanemura, Yonehiro; Tanino, Mishie; Nakanishi, Katsuyuki; et al.
Abstract: Purpose: The current study aims to test the hypothesis that the ratio of T1-weighted image to T2-weighted image signal intensity (T1w/T2w-Ratio: rT1/T2), an imaging surrogate developed for myelin integrity, is predictive of histologically lower-grade glioma's IDH mutation status. Materials and Methods: 25 histologically and molecularly confirmed lower-grade glioma patients with eight IDH-wildtype (IDHwt) and 17 IDH-mutant (IDHmt) tumors at Asahikawa Medical University Hospital (AMUH) were used as a test cohort. Twenty-nine patients (IDHwt: 13, IDHmt: 16) from Osaka International Cancer Institute (OICI) and 101 patients from the Cancer Imaging Archive (TCIA) / Cancer Genome Atlas (TCGA) dataset (IDHwt: 19, IDHmt: 82) were used as external cohorts. rT1/T2 images were calculated from T1- and T2-weighted images using a recommended signal correction. The relationship between the mean rT1/T2 (mrT1/T2) and the IDH mutation status was investigated. Moreover, t-Distributed Stochastic Neighbor Embedding (t-SNE) investigated the difference in MRI qualities and characteristics between the three cohorts. Results: The test cohort at AMUH revealed that mrT1/T2 of IDHwt tumors was significantly higher than that of IDHmt tumors (p < 0.05) and that the optimal cut-off of mrT1/T2 for discriminating IDHmt was 0.666-0.677, (AUC = 0.75, p < 0.05), which finding was validated by the external domestic cohort at OICI (AUC = 0.75, p = 0.02). However, the external international cohort deriving from TCIA/TCGA could not validate this (AUC = 0.63, p = 0.08). t-SNE analysis revealed that the difference in image characteristics within the cohort was more diverse for the TCIA/TCGA than for the two domestic cohorts. Conclusion: The current study revealed that mrT1/T2 was able to discriminate IDHwt and IDHmt tumors in two domestic cohorts significantly. This was not validated by the TCIA/TCGA cohort due to the wide variety in the original imaging characteristics of the TCIA/TCGA cohort.